Pembangunan Sistem lnformasi Manajemen Travel Berbasis Web (Studi Kasus: Travel Lia Jaya Sentosa) - Rizky Brama Sakti; Nurudin Santoso; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Lia Jaya Sentosa is a travel company that operates in the field of car rental to deliver passengers to certain cities. Based on interviews conducted, there is inefficiency in the departure schedule search activities, operators must look into the ledger first to check the departure schedule that is still available, causing prospective passengers to wait long enough just to find out the empty schedule. In addition, in the process of recording orders that occur, recording is usually carried out in a ledger, then every month it will be recapitulated into Microsoft Excel files. This will certainly make the operator work twice because in addition to recording it, then the operator must recap it into a report into Microsoft Excel files so that it will make it less effective and efficient. Therefore, to facilitate data processing starting from recording, ordering to making reports, it is necessary to have a system that can handle these things. The development of this system uses the waterfall method, which the process starts from the analysis of system requirements carried out by conducting interviews with Lia Jaya Sentosa travel operators. Then the design phase is carried out which is divided into architectural design, component design, data design and interface design. Then the implementation phase realizes the system to be built in accordance with the design that has been made, both of which are carried out with an object oriented approach. The results of unit system testing are 100% valid, 100% integration testing is valid, 100% validation testing is valid and in usability testing is a system built that can facilitate existing work in the company based on the SUS (System Usability Scale) score obtained 83,5.